Existence of Weak Solutions for Weighted Robin Problem Involving p.-biharmonic operator - Kulak, Öznur; Aydin, Ismail; Unal, Cihan (Differential equations and dynamical systems, 2024)
Using Mountain Pass Theorem, we consider the existence of weak solutions of weighted Robin problem involving p . -biharmonic operator a x Δ p x 2 u = λ b ( x ) u q ( x ) - 2 u , i n Ω a ( x ) Δ u p ( x ) - 2 ∂ u ∂ υ + β ( x ) u p ( x ) - 2 u = 0 , o n ∂ Ω under some conditions in the space W a , b 2 , p ( . ) Ω .